The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/21691401.2018.1452251
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial detection using bacteriophages and gold nanorods by following time-dependent changes in Raman spectral signals

Abstract: This study attemps to develop bacterial detection strategies using bacteriophages and gold nanorods (GNRs) by Raman spectral analysis. Escherichia coli was selected as the target and its specific phage was used as the bioprobe. Target bacteria and phages were propagated/purified by traditional techniques. GNRs were synthesized by using hexadecyltrimethyl ammonium bromide (CTAB) as stabilizer. A two-step detection strategy was applied: Firstly, the target bacteria were interacted with GNRs in suspensions, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…The detection of bacterial pathogens such as Pseudomonas fluorescens (P. fluorescens) is of significant interest both in life science and in environmental research, due to the fact that microbial contamination can result in significant health concern. In this study, we have investigated the use of a microfabricated chip device in the detection of P. fluorescens and Pseudomonas putida (P.…”
Section: Resultsmentioning
confidence: 99%
“…The detection of bacterial pathogens such as Pseudomonas fluorescens (P. fluorescens) is of significant interest both in life science and in environmental research, due to the fact that microbial contamination can result in significant health concern. In this study, we have investigated the use of a microfabricated chip device in the detection of P. fluorescens and Pseudomonas putida (P.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of gold nanorods (AuNRs) is of considerable interest owing to their unique optical properties, which can be used for imaging, surface‐enhanced Raman spectroscopy (SERS), diagnostics, sensing, and biological applications . Murphy et al .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of gold nanorods (AuNRs)i so fc onsiderable interest owing to their unique optical properties,w hich can be used for imaging, [1][2][3][4][5][6][7][8] surface-enhanced Raman spectroscopy (SERS), [9][10][11][12] diagnostics, [13][14][15] sensing, [16,17] and biologicala pplications. [18][19][20][21][22][23][24] Murphy et al [25] first reported the seed-mediated chemicals ynthesis of AuNRs.…”
Section: Introductionmentioning
confidence: 99%
“…4e, Supplementary Fig. 25) [55,[60][61][62][63][64][65][66][67][68][69][70]. We specifically note that peaks at 732.5 and 1330 cm -1 from our S. epi -containing samples are attributed to purine ring-breathing modes [65] and the Adenine part of the flavin derivatives or glycosidic ring mode of polysaccharides [64]; peaks at 755 and 1450 cm -1 from our E. coli -containing samples are attributed to Tryptophan ring breathing [70] and CH 2 /CH 3 deformation of proteins and lipids [62]; and peaks at 482 and 1124 cm -1 from our RBC-containing samples are attributed to γ12 out of plane deformation of porphyrin, a main component of hemoglobin [67], and ν13 or ν42 valence [68].…”
Section: Multi-cellular Droplet Classification and Raman Feature Impo...mentioning
confidence: 99%